An Alternative and Conserved Cell Wall Enzyme That Can Substitute for the Lipid II Synthase MurG - L. Zhang (American Society for Microbiology, 2021)
Almost all bacteria are surrounded by a cell wall, which protects cells from environmental harm. Formation of the cell wall requires the precursor molecule lipid II, which in bacteria is universally synthesized by the conserved and essential lipid II synthase MurG.